Application of agile methods in industrial electronics education; lessons learned from a case study - Ul Amin, R.; Aijun, L.; Inayat, I. (Inderscience, 2015)
This paper presents the introduction of agile methods to the study of industrial electronics education as performed at a public sector university in Pakistan. The application of agile methods i.e. scrum to the projects of industrial electronics course; industrial automation and process control proved to be an innovative and favourable alternative to the previously used traditional phase driven approaches. The emphasis of agile methods on iterative development, team collaboration, and quick feedback are the reasons which triggered the ease and favourability. The quick feedback and incremental development helped the students to improve and revisit their shortcomings and deliver within time. The cross functional teams enabled the students to deal with process management throughout the product development. The findings of the study state that the flexible yet time critical agile methods pledge benefits in meeting ever changing and evolving industry requirements.